CAC-MAC: A Cross-Layer Adaptive Cooperative MAC for Wireless Ad Hoc Networks. (14th May 2012) - Shi, Chunguang; Zhao, Haitao; Wang, Shan; Wei, Jibo; Zheng, Linhua
Abstract : Cooperative communication has been recently proposed as a way to mitigate fading in wireless networks. A cross-layer adaptive cooperative MAC (CAC-MAC) protocol for IEEE 802.11 DCF-based wireless ad hoc networks is proposed. The novel aspect and core idea of our proposal is a cross-layer adaptive data transmission algorithm considering both the length of data frame at the MAC layer and instantaneous wireless channel conditions. Under this algorithm, direct transmission mode or proper cooperative transmission mode will be adaptively selected for data packets according to both MAC layer and physical layer information. Analytical results demonstrate the effectiveness of the adaptive data transmission algorithm. Simulation studies based on NS2 show that the CAC-MAC protocol can significantly improve network throughput and reduce packet delay compared with legacy IEEE 802.11 protocol, which illustrate a new paradigm for realistic cross-layer cooperative MAC protocol design for next-generation wireless ad hoc networks.